2007
DOI: 10.1073/pnas.0703151104
|View full text |Cite
|
Sign up to set email alerts
|

A proposed signaling motif for nuclear import in mRNA processing via the formation of arginine claw

Abstract: Phosphorylation of proteins by kinases is the most commonly studied class of posttranslational modification, yet its structural consequences are not well understood. The human SR (serinearginine) protein ASF/SF2 relies on the processive phosphorylation of the serine residues of eight consecutive arginine-serine (RS) dipeptide repeats at the C terminus by SRPK1 before it can be transported into the nucleus. This SR protein plays critical roles in spliceosome assembly, pre-mRNA splicing, and mRNA export, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 34 publications
7
80
3
1
Order By: Relevance
“…This hypothesis has been validated in recent experimental studies (Collins, et al, 2008; Gsponer, et al, 2008) and in several cases disorder-to-order transition upon phosphorylation has been predicted (Espinoza-Fonseca, et al, 2007; Hamelberg, et al, 2007; Hegedus, et al, 2008). Furthermore, it has recently been shown that disordered proteins are substrates of twice as many kinases as are ordered proteins (Gsponer, et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…This hypothesis has been validated in recent experimental studies (Collins, et al, 2008; Gsponer, et al, 2008) and in several cases disorder-to-order transition upon phosphorylation has been predicted (Espinoza-Fonseca, et al, 2007; Hamelberg, et al, 2007; Hegedus, et al, 2008). Furthermore, it has recently been shown that disordered proteins are substrates of twice as many kinases as are ordered proteins (Gsponer, et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…4). In addition, the formation of similar stable R-pS salt bridges has been proposed in hyperphosphorylated RS dipeptide repeat motifs (50).…”
Section: Discussionmentioning
confidence: 99%
“…Although RRMs bind pre-mRNA and are generally well-characterized at the structural level, RS domain structure and function is still not fully understood. RS domains are disordered but they become more rigid upon phosphorylation based on NMR studies 9, 11 . However, owing to their poor solubility and self-association, no high-resolution structure of a full-length SR protein has been reported.…”
Section: Introductionmentioning
confidence: 99%